(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
Chitin was prepared from prawn shell waste by a chemical process involving demineralization, deproteinization and decolorization. Chitosan was prepared from chitin by deacetylation. The present study was undertaken to evaluate the influence of deacetylation process during chitosan production on the physiochemical and functional properties of prawn shell chitosan. Four experimental chitosan samples were prepared at ambient temperature with different duration of deacetylation process (i.e. 45, 55, 65 and 72 hrs and their characteristics were evaluated. This study demonstrated that duration of deacetylation affected mostly the degree of deacetylation, solubility and viscosity of the product. Therefore, the process of deacetylation of chitin for conversion to chitosan needs careful control and observation. Key words: Prawn shell; Duration of Deacetylation; Chitosan; Ambient temperature; Physicochemical and Functional properties. DOI: 10.3329/bjsir.v45i4.7330 Bangladesh J. Sci. Ind. Res. 45(4), 323-330, 2010